Service period as a moderator to the behaviour and work performance relationship in the organisation - Othman K.; Ismail S.N.; Mohd Fuad S.H.; Md Hasim M.; Othman F.; Abdullah M.R.; Zaidi N.; Addenan N.A.; Nik Nazli N.N.N. (Penerbit Universiti Sains Malaysia, 2024)
Indexed by SCOPUS/ERA